Penerapan Sistem Informasi Manajemen Sekolah untuk Meningkatkan Kualitas Layanan Pendidikan di MTs Daarul Muttaqiin Cimahi Cimahi - Ropik, Ikbal; Nugraha, Mulyawan Safwandy (LPPPI Publishing, 2025)
Education plays an important role in shaping quality human resources, especially in the digital era that demands efficiency and transparency in school management. This study aims to describe the implementation of the school's Management Information System (SIM) in improving the quality of education services at MTs Daarul Muttaqiin Cimahi, as well as identify obstacles and efforts to overcome them. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation studies. The results showed that the implementation of SIM at MTs Daarul Muttaqiin Cimahi has helped improve the efficiency of data management of students, teachers, financial administration, and facilities and infrastructure. The positive impacts include the acceleration of administrative processes, increased information transparency, and support for data-based decision making. However, the implementation of SIM still faces several obstacles, such as limited technological infrastructure, lack of professionals in the field of information technology, and limited skills of teaching and education personnel in operating the system. To overcome these obstacles, the school has made various efforts, including the procurement of technology equipment through government assistance, regular training for education personnel, and cooperation with third parties for system development. With these efforts, SIM is expected to continue to be optimized to improve the quality of education services at MTs Daarul Muttaqiin Cimahi.